School Nurses' Perspectives on Health among School-Aged Children and Adolescents During the COVID-19 Pandemic. (April 2023) - Garmy, Pernilla; Rahr, Charlotta; Persson, Louise; Einberg, Eva-Lena
The aim of this study was to investigate school nurses' perspectives on students' health during the COVID-19 pandemic in Sweden in 2021. A cross-sectional survey design was used with school nurses (n = 225) working in schools in Sweden from elementary to upper secondary levels. The Clausson School Nurse Perception Questionnaire was used with two additional questions about the COVID-19 pandemic. The school nurses rated students' physical health as very good or good in 78% of the cases and their mental health as very good or good in 64%. There was also a negative trend in mental health during the pandemic, especially among girls. School nurses working in vulnerable areas (i.e., areas with a high proportion of immigrants and those receiving financial assistance) rated students' physical and mental health significantly worse compared other areas.